Robustness Disparities in Phi-3-Mini and Mistral-7B on Adversarial GSM-Symbolic Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 15 peer-reviewed papers addressing the following research question: How does the robustness of Phi-3-mini and Mistral-7B-v0.1 vary when evaluated on adversarially perturbed GSM-Symbolic instances versus clean instances across multiple languages, using accuracy and. 13 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 2.5/10. This report i
Machine-generated literature synthesis.